(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
As a result of the active influence of man on the soil, a change in its properties, an increase or decrease in fertility, salinity, erosion, degumification, rational use of non-irrigated lalmi lands in farming, its protection requires even more attention than before. It is required to rationally use the land, increase the fertility of the soil, know its quality, economic assessment, protection, plant various plants in a row, scientifically based on the condition of the soil, methods of environmentally "clean" processing of soil, carry out fertilizing at a high level. Increasing the fertility and production capacity of the soil should largely depend on the careful and economical treatment of it, its complex aimed at improving it.